Healthy diets: A privilege of the rich? - Hirvonen, Kalle (DLG-Verlag GmbH, 2020)
A healthy and diversified diet is the best antidote against hidden hunger. But by no means everyone can afford such a diet – quite apart from the fact that there is no uniform definition of it. Our author shows what affordability is like around the world and which approaches can lead to a world free of hidden hunger.